Mindful Eating: Connecting With the Wise Self, the Spiritual Self - Kristeller, Jean L.; Jordan, Kevin D. (Frontiers in Psychology, 2018)
In the Mindfulness-Based Eating Awareness Training program (MB-EAT) (Kristeller and Wolever, 2014; Kristeller and Wolever, in press), mindfulness practice is taught, mindful eating is cultivated, and self-acceptance and spiritual well-being are enhanced. An integrative concept is the value of cultivating ‘wisdom’ in regard to creating a new and sustainable relationship to eating and food. ‘Wisdom’ refers to drawing on personal experience and understanding in a flexible, insightful manner, rather than strictly following external rules and guidelines. Several clinical trials involving variations of MB-EAT have documented substantive improvement in how people relate to their eating, including individuals with both binge eating disorder (BED) and subclinical eating issues. Based on the traditional value of contemplative practices for cultivating spiritual engagement, and on evidence from related research showing that spiritual well-being increases in the Mindfulness-Based Stress Reduction (MBSR) program and is related to other effects, we hypothesized that the MB-EAT program would also engage this aspect of experience, as assessed by the Functional Assessment of Chronic Illness Therapy – Spiritual Well-Being subscale (FACIT-Sp), and that increases in spiritual well-being would relate to other measures of adjustment such as emotional balance and improvement in disordered eating. Participants (N = 117) with moderate to morbid obesity, including 25.6% with BED, were randomly assigned to MB-EAT or a wait-list control, and assessed on the FACIT-Sp and other measures at baseline, immediate post (IP), and 2-month followup (F/Up). Both FACIT-Sp factors [Meaning/Peace (M/P) and Faith] increased significantly in the MB-EAT group and were stable/decreased in the control group. Increases in these factors related to improvement in emotional adjustment and eating regulation at IP and at F/Up, and to increases in aspects of mindfulness measured by the Five Facet Mindfulness Questionnaire (FFMQ). Increases in M/P during treatment mediated effects of the FFMQ Observe factor on eating regulation and depression at IP. Results are discussed in terms of the role that mindfulness practice plays in cultivating ‘wise mind’ and the related value of spirituality. It is argued that the core elements of the MB-EAT program lead to meaningful spiritual engagement, which plays a role in people’s ability to improve and maintain overall self-regulation.